Pengaruh Fasilitas Pendidikan Terhadap Prestasi Kerja Guru dengan Semangat Kerja Sebagai Variabel Intervening: (Studi pada Guru SMP Negeri 1 Torjun Kabupaten Sampang) - Mei Indrawati; Sri Saniyah; Rusdiyanto Rusdiyanto (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
Sri Saniyah, 2024. The Influence of Educational Facilities on Teacher Work Performance with Teacher Work Morale as an Intervening Variable. Wijaya Putra University Postgraduate Program Surabaya. This type of research is explanatory research, the approach used is a quantitative approach, the research sample is 42 respondents. The analysis tool uses Smart PLS (Partial Least Square). Research objectives: 1) To describe educational facilities, work enthusiasm and teacher work performance at SMP Negeri 1 Torjun, Sampang Regency. 2) To test and analyze whether educational facilities have a significant effect on teacher work performance at SMP Negeri 1 Torjun, Sampang Regency. 3) To test and analyze whether teacher work enthusiasm has a significant effect on the work performance of teachers at SMP Negeri 1 Torjun, Sampang Regency. 4) To test and analyze whether educational facilities have a significant effect on the work spirit of teachers at SMP Negeri 1 Torjun, Sampang Regency. 5) To test and analyze whether educational facilities have a significant indirect effect on the work performance of teachers at SMP Negeri 1 Torjun Sampang Regency with work enthusiasm as an intervening variable. The research results show that: 1) Educational facilities have a significant effect on teacher work performance as evidenced by a p value of 0.039. 2) Educational facilities have a significant effect on work morale as evidenced by the p value of 0.002. 3) Teacher morale has a significant effect on teacher work performance as evidenced by a value of 0.001. 4) Educational facilities on teacher work performance with teacher work enthusiasm as an intervening variable have a significant effect with a p value of 0.040.